Writing labour stone quarry workers in Delhi - Talib, Mohammad (New Delhi ; Oxford : Oxford University Press, 2010)
Drawing from the author's intensive fieldwork, this book examines stone-quarry workers on the expanding fringes of south Delhi and offers ways to enter and interpret their world. The study views them as active agents negotiating extreme poverty exploitation, and oppression.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Quarries and quarrying -- India -- Delhi -- Employees; Working class -- India -- Delhi